Linked administrative data’s role in Victoria’s first social impact investment, journey to social inclusion, working to end chronic homelessness - Findlay, Suzanne (International Journal of Population Data Science, 2020)
Introduction Indigenous people worldwide are overrepresented and adversely effected by diabetes and its complications. Optimal glycemic control and lipid monitoring is fundamental to the management of diabetes. This study linked population level data to assess monitoring, treatment and control of blood sugars and lipids in First Nations’ people in Ontario. Objectives and Approach We linked 17 Ontario population-based health administration datasets at the individual level with the Indian Register dataset. The latter provides information on all registered or Status First Nations people in Canada . Age and sex-adjusted rates of HbA1c and lipid monitoring were calculated for each 12-month period from April 1, 1995, to March 31, 2015.). We assessed the proportion of individuals with diabetes whose HbA1c and lipid values were controlled. To capture prescriptions for antidiabetic drugs, we used the Drug Identification Number database to identify all antidiabetic drugs and linked these to the Ontario Drug Benefit database to capture prescription information. Results Compared with other people in Ontario, First Nations people with diabetes are monitored less for key indicators of diabetes control. In 2014/15, 37.0% of First Nations people with diabetes living in First Nations communities had their blood sugar levels monitored compared to 45.0% of other people in Ontario. A similar pattern was shown for lipid level monitoring, with 48.3% of First Nations people living in First Nations communities, and 65.8% of other people in Ontario having recorded lipid measurements. Conclusion / Implications Early screening for complications and screening for hemoglobin A1c is strongly recommended.